Epidemiological profile and costs of hospitalizations for migraines in Paraná between 2014 and 2023 - Lazzaron, Paola Regina Mombach; Ishie, Heitor Tadayuki; Ishie, Sofia Mitsue; Iocohama, Thiago De Carvalho; Ruths, Jéssica Cristina; Machado, Sabrina Lima (Headache Medicine, 2024)
Introduction: Headaches represent common complaints in medical care and an important cause of morbidity worldwide, often resulting in hospital admissions. Headaches have significant repercussions for public health, according to the literature, affecting between 43% and 93% of the Brazilian population, potentially impairing quality of life. The most affected group comprises women, young adults, black, and brown people. The number of hospitalizations for this condition is higher in the Southeast, Northeast, and South regions. Objective: To identify the epidemiological profile and the cost of hospitalizations for headaches in Paraná from 2014 to 2023. Methods: Observational, descriptive, quantitative, and cross-sectional study. Based on secondary data from the Sistema de Informações Hospitalares do Sistema Único de Saúde (SIH/SUS) of the Departamento de Informação e Informática do Sistema Único de Saúde (DATASUS). The analyzed variables were age, sex, color or race, total value, average value, and average length of stay. Results: In Paraná, between 2014 and 2023, there were 14.578 hospitalizations for migraine and other headache syndromes. The year 2019 stands out with 2.833 hospitalizations. There was a prevalence of hospitalizations in women (9.068), in white individuals (11.488), and aged between 40 to 49 years (2.640 cases). The majority of hospitalizations were urgent (13.582). The total cost of hospitalizations was R7.743,620.00 with an average annual cost of R490.21 per hospitalization and an average duration of 2.7 days. Conclusion: There was correspondence between the epidemiological profile found in the state of Paraná and what is observed in the current literature, showing a high number of hospitalizations for migraine and other headache syndromes, with significant expenditure on the public health system, requiring further investigation into the causality of these events, so that, the prevention of crises can be intensified within the most affected group.